Sequential Fermentation with Torulapora delbrueckii and selected Saccharomyces cerevisiae for aroma enhancement of Longyan dry white Wine. (13th November 2021) - Wang, Suwen; Lu, Yao; Fu, Xiaofang; Wang, Meiqi; Wang, Wenxiu; Wang, Jie; Wang, Huanxiang; Liu, Yaqiong
Abstract: In order to evaluate the effects of yeast starter on the quality and flavour profile of Longyan dry white wine, pure fermentation and sequential fermentation of selected Torulaspora delbrueckii and selected Saccharomyces cerevisiae (VL2, DELTA, X5) were performed in industrial‐scale fermentation of this work. Compared with pure fermentation, sequential fermentation improved the fermentative aroma concentrations, especially the treatment of T . delbrueckii/ DELTA increased the content of ethyl butyrate, ethyl caprylate and ethyl decanoate, which may be related to a strong citrus fruity aroma. Principal component analysis revealed a significant difference in aromatic feature of co‐fermentation of T. delbrueckii /DELTA and T. delbrueckii /VL2 from their respective pure fermentation. These may be related to amino acid metabolism and further affected the formation of volatile compounds according to correlation analysis. Overall, sequential fermentation using DELTA and T. delbrueckii strengthened the aroma characteristics and improved the complex of wines. It will provide a new strategy to regulate the flavour and improve the quality of Longyan dry white wine. Abstract : The fermentation process of Longyan dry white wine.